Reconstruction of the spectral type of limiting distributions in dynamical conflict systems - Koshmanenko, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish the conditions of reconstruction of pure spectral types (pure point, pure absolutely continuous, or pure singularly continuous spectra) in the limiting distributions of dynamical systems with compositions of alternative conflict. In particular, it is shown that the point spectrum can be reconstructed starting from the states with pure singularly continuous spectra.